Monitoring scrub weed change in the Canterbury region using satellite imagery - Shepherd, J.D.; Dymond, J.R.; Cuff, J.R.I. (New Zealand Plant Protection, 2007)
The spatial change of woody vegetation in the Canterbury region was automatically mapped between 1990 and 2001 using Landsat satellite image mosaics The intersection of valid data from these mosaics gave coverage of 84 of the Canterbury region Changes in woody cover greater than 5 ha were identified Of the 5 ha areas of woody change only those that were likely to have been a scrub change were selected using ancillary thematic data for current vegetation cover (eg afforestation and deforestation were excluded) This resulted in 2466 polygons of potential scrub change These polygons were rapidly checked by visual assessment of the satellite imagery and assigned to exotic or indigenous scrub change categories Between 1990 and 2001 the total scrub weed area in the Canterbury region increased by 3600 400 ha and indigenous scrub increased by 2300 400 ha